A filtered life - Taylor, Nicole, 1972- author.
1 online resource
Keywords: "A Filtered Life is the first comprehensive ethnographic account to explore how college students create and manage multiple identities on social media. Drawing on interviews and digital ethnographic data gleaned from popular social media platforms, the authors document and make visible routinized practices that are typically hidden and operating behind the scenes. They introduce the concept of 'digital multiples', wherein students strategically present themselves differently across social media platforms. This requires both the copious production of content and the calculated development of an instantly recognizable aesthetic or brand. Taylor and Nichter examine key contradictions that emerged from student narratives, including presenting a self that is both authentic and highly edited, appearing upbeat even during emotionally difficult times, and exuding body positivity even when frustrated with how you look. Students struggled with this series of impossibilities; yet, they felt compelled to maintain a vibrant online presence. With its close-up portrayal of the social and embodied experiences of college students, A Filtered Life is ideal for students and scholars interested in youth studies, digital ethnography, communication and new forms of media"--